Barriers for Junior Doctors to Specialize in Rural Generalism – A Medical Student Experience - Cox, Madeleine J. (International Journal of Medical Students, 2023)
Australia is an exceptional country, with the majority of its population living on the Eastern Seaboard in highly urbanized, developed capital cities such as Sydney, Melbourne, and Brisbane. However, more than seven million Australian’s live inland in some of the flattest, driest, and inhabitable regions on Earth.1 This provides unique challenges to Australia’s regional country towns, as they battle issues such as isolation, substandard health resources and poor welfare. Despite Australia’s world class healthcare system, unfortunately individual’s living in regional Australia, have health comparable to that of low and middle income countries.2 Government strategies have aimed to improve this through lackluster funding, empty promises, and ill-considered pathway strategies.